Daytime naps and depression risk: A meta-analysis of observational studies - Li, Liqing; Zhang, Qi; Zhu, Liyong; Zeng, Guohua; Huang, Hongwei; Zhuge, Jian; Kuang, Xiaorui; Yang, Sule; Yang, Di; Chen, Zhensheng; Gan, Yong; Lu, Zuxun; et al. (Frontiers in Psychology, 2022)
Background The relationship between daytime napping and depression remains debatable. Thus, a meta-analysis in this study was conducted to evaluate the relationship between daytime napping and depression. Methods The PubMed, Embase, Web of Science, and China National Knowledge Infrastructure databases were searched up to February 2022, and the reference lists of the included studies were also retrieved. A random-effects model was used to estimate the combined effect size. Results Nine studies with 649,111 participants were included in the final analysis. The pooled odds ratio (OR) was 1.15 (95% confidence interval: 1.01–1.31) with a significant heterogeneity (I2 = 91.3%, P for heterogeneity <0.001), and the results demonstrated an increased risk of depressive symptoms among daytime nappers. Visual inspection of the funnel plot and Egger's and Begg's tests identified no obvious evidence of publication bias. Conclusion This meta-analysis indicates that daytime naps are a predictor of depression. The effects of daytime napping on depression may vary depending on the characteristics of people, the pattern of naps, and the individual's sleep experience. The findings may have significant implications for future research on depression.